2005
DOI: 10.1055/s-2004-813931
|View full text |Cite
|
Sign up to set email alerts
|

Zur Differenzialdiagnostik des „signalkompromittierten” Os lunatum in der MR-Tomographie

Abstract: The lunate may be affected by different pathological states of the wrist. In total, only one quarter of the signal-compromised lunate represented Kienboeck's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In total, 3581 citations were initially identified, and seventy-four of them were deemed potentially relevant. On full review of the twentyseven studies that initially satisfied the eligibility criteria, four were excluded because they did not provide sufficient data for meta-analysis after attempts were made to contact the respective corresponding authors 24,34-36 , one paper did not present the results of the TFCC assessment 37 , and one paper 38 was a dual publication to a second paper 39 . In this final case, only the earlier publication was included in the final review.…”
Section: Search Resultsmentioning
confidence: 99%
“…In total, 3581 citations were initially identified, and seventy-four of them were deemed potentially relevant. On full review of the twentyseven studies that initially satisfied the eligibility criteria, four were excluded because they did not provide sufficient data for meta-analysis after attempts were made to contact the respective corresponding authors 24,34-36 , one paper did not present the results of the TFCC assessment 37 , and one paper 38 was a dual publication to a second paper 39 . In this final case, only the earlier publication was included in the final review.…”
Section: Search Resultsmentioning
confidence: 99%
“…Radiographs were non-specific and MRI showed lunate bone marrow oedema in short T1 inversion recovery (STIR) and T1 weighted sequences without a fracture line (fig 4). Schmitt et al 41 have reported Kienbock's disease as the most common cause of abnormal signal intensity in the lunate on MRI, followed by ulnolunate impaction syndromes and intraosseous ganglion. Lunate stress fracture should be differentiated from osteonecrosis and should be considered in the differential diagnosis in athletes complaining of dorsal wrist pain.…”
Section: Discussionmentioning
confidence: 99%
“…as cellulitis, infectious arthritis or gout [ 17 ]. In addition, there are some important differential diagnoses in particular the bone marrow oedema of the lunate, which can usually be resolved radiologically based on the distribution pattern of the oedema, lunate and carpal morphology, ulnar variance, as well as clinical symptoms [ 19 , 20 ]: (a) Kienböck’s disease is often associated with ulnar minus variance, proximal necrosis zone and radial localized bone marrow oedema. (b) Ulnar impaction syndrome shows signal alterations at the ulnar side of the lunate, usually positive ulnar variance, and triangular fibrocartilage complex (TFCC) perforation.…”
Section: Discussionmentioning
confidence: 99%